Collection of microorganisms with potential as additives for animal nutrition at the Institute of Animal Science - Sosa, Areadne; González, Niurca; García, Yaneisy; Marrero, Yoandra; Valiño, Elaine; Galindo, Juana; Sosa, Dailyn; Alberto, Maryen; Roque, Dayamí; Albelo, Nereida; Colomina, Laura; Moreira, Onidia (Cuban Journal of Agricultural Science, 2018)
The supply of viable, authentic and secure microbial cultures is essential for obtaining agricultural products through biotechnology. The objective of this study was to establish, at the Institute of Animal Science, the methodology for organizing and managing the collection of microorganisms with potential as additives in animal nutrition. The establishment of the collection was developed in three stages: design of collection structure, definition of conservation methods for each type of microorganism and preparation of documents. Guidelines of the World Federation for Culture Collections, biological safety regulations, requirements of quality systems and requirements for lab competence were consulted. The establishment of a collection of microorganisms at the Institute of Animal Science, with appropriate conservation methods for each microbial group, guarantees the availability of strains for teaching, research and obtaining additives for animal feed. Key words: culture collection, conservation of microorganisms, microbial additives